How to Influence Your Attitude to Man (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
the relevance of this problem lies in the fact that the relationship of a person to a person is formed as a conscious, selective connection of subject with subject, its initial and resulting moment has a relationship with another person, develops as the internal content of communication and interaction with him, is realized and manifested in the organization by a person the ways and forms of his ideal or real behavior in relation to another person, constituting the content of a special activity the subject of which is another person.